Comparison of Chemical Analysis of Compost Leachate and Commercial Fertilizer to check the quantity of heavy metals - Ameen, Ayesha (International Journal of Psychosocial Rehabilitation, 2020)
Leachate can be defined as a liquid that can probably pollute environment. This leachate is produced during aerobic composting of organic waste that may lead to many harmful effects on soil, surrounding villages, aquatic life and groundwater resources. Solid waste Compost Leachate is a liquid that produced during organic solid waste composting and brings out heterogeneous materials of and contains a complex diversity of organic compounds and materials such as heavy metals, fatty acids, humic acid substances, and many toxic compounds. This study was designed to compare the concentration of heavy metals present in compost leachate prepared during composing of municipal solid waste and commercial fertilizer. Municipal solid waste compost leachate and commercial fertilizer were properly evaluated for the physico-chemical parameters. Samples of leachate prepared from municipal solid waste composting were collected from Lahore Compost Company. Samples were digested and analysed in duplicates for pH, Temperature, BOD, EC, TDS and COD. The metals such as Ni, Cr, Zn, and Cu quantity in the leachate was also determined using the Atomic Absorption. It was concluded from this study that the quantity of heavy metals (Cu, Ni, Zn, and Cr) present in leachate was within acceptable amount that is also not harmful for plan and crop growth. On comparison with commercial fertilizer this amount of heavy metals is also lower than the commercial fertilizer. It was concluded from this study that the use compost leachate for plants and other crops is safe.